HYSTEROTOMY THROUGH COLPOTOMY COMBINED WITH CERVICOTOMY FOR THE TREATMENT OF FETAL MACERATION IN A CATTLE - PRAKASH, S; SELVARAJU, M; RAVIKUMAR, K; MANOKARAN, S; PALANISAMY, M (The Indian Journal of Animal Reproduction, 2016)
Five year-old Jersey crossbred cattle was diagnosed as suffering from fetal maceration. The macerated fetal bones along with tissue debris were removed by hysterotomy through colpotomy combined with cervicotomy approach.